Human Antibodies Targeting Influenza B Virus Neuraminidase Active Site Are Broadly Protective - Madsen, Anders; Dai, Ya-Nan; McMahon, Meagan; Schmitz, Aaron J.; Turner, Jackson S.; Tan, Jessica; Lei, Tingting; Alsoussi, Wafaa B.; Strohmeier, Shirin; Amor, Mostafa; Mohammed, Bassem M.; Mudd, Philip A.; et al. (Immunity (Cambridge, Mass.), 2020)
Influenza B virus (IBV) infections can cause severe disease in children and the elderly. Commonly used antivirals have lower clinical effectiveness against IBV compared to influenza A viruses (IAV). Neuraminidase (NA), the second major surface protein on the influenza virus, is emerging as a target of broadly protective antibodies that recognize the NA active site of IAVs. However, similarly broadly protective antibodies against IBV NA have not been identified. Here, we isolated and characterized human monoclonal antibodies (mAbs) that target IBV NA from an IBV-infected patient. Two mAbs displayed broad and potent capacity to inhibit IBV NA enzymatic activity, neutralize the virus in vitro, and protect against lethal IBV infection in mice in prophylactic and therapeutic settings. These mAbs inserted long CDR-H3 loops into the NA active site, engaging residues highly conserved among IBV NAs. These mAbs provide a blueprint for the development of improved vaccines and therapeutics against IBVs. [Display omitted] •Generation of seven human monoclonal antibodies to influenza B virus neuraminidase•Two antibodies, 1G05 and 2E01, are broadly cross-reactive•1G05 and 2E01 are potently protective against lethal Influenza B infection in mice•1G05 and 2E01 bind conserved residues in the Influenza B neuraminidase active site Influenza B virus (IBV) infections cause severe disease. Madsen et al. develop and characterize human monoclonal antibodies that possess broad and potent capacities to inhibit IBV neuraminidase enzymatic activity, neutralize the virus in vitro, and protect against lethal IBV infection in mice in prophylactic and therapeutic settings.